An in situ phosphorus source for the synthesis of Cu3P and the subsequent conversion to Cu3PS4 nanoparticle clusters. Issue 23 (13th November 2015) - Sheets, Erik J.; Yang, Wei-Chang; Balow, Robert B.; Wang, Yunjie; Walker, Bryce C.; Stach, Eric A.; Agrawal, Rakesh
Abstract: Abstract : The search for alternative earth abundant semiconducting nanocrystals for sustainable energy applications has brought forth the need for nanoscale syntheses beyond bulk synthesis routes. Of particular interest are metal phosphides and derivative I–V–VI chalcogenides including copper phosphide (Cu3 P) and copper thiophosphate (Cu3 PS4 ). Herein, we report a one-pot, solution-based synthesis of Cu3 P nanocrystals utilizing an in situ phosphorus source: phosphorus pentasulfide (P2 S5 ) in trioctylphosphine. By injecting this phosphorus source into a copper solution in oleylamine, uniform and size controlled Cu3 P nanocrystals with a phosphorous-rich surface are synthesized. The subsequent reaction of the Cu3 P nanocrystals with decomposing thiourea forms nanoscale Cu3 PS4 particles having p-type conductivity and an effective optical band gap of 2.36 eV. The synthesized Cu3 PS4 produces a cathodic photocurrent during photoelectrochemical measurements, demonstrating its application as a light-absorbing material. Our process creates opportunities to explore other solution-based metal-phosphorus systems and their subsequent sulfurization for earth abundant, alternative energy materials.